Newer preparation methods relating to smart nanomaterial solutions and environmental science - Otun K.O.; Amusat S.O.; Musa A.O.; Kareem A.O.; Idris A.O.; Mukhtar A. (Elsevier, 2025)
By carefully regulating the physicochemical properties of nanomaterials such as size and morphology, the properties of nanomaterials can be tuned to meet specific demands. However, due to the limitations associated with the use of nanomaterials in environmental science such as toxicity, biocompatibility, and ease of tunability, smart nanomaterials have been developed. Smart nanomaterials respond to changes in their environments and function based on these changes. The approaches guiding the synthesis of smart nanomaterials are not entirely different from ordinary nanomaterials and can be chiefly grouped into top-down (milling, laser ablation, and sputtering) and bottom-up (chemical vapor deposition, coprecipitation, hydrothermal, and sol-gel) methods. This chapter focuses on the newer preparation methods including green and three-dimensional (3D) printing techniques relating to smart nanomaterial solutions and environmental science. While we emphasize the properties and applications of smart nanomaterials at every turn, the merits and demerits of each preparation technique are highlighted. We conclude by discussing the challenges and prospects of smart nanomaterials in environmental science. We hope that researchers and materials scientists will find this chapter useful for enhancing the properties of nanomaterials for environmental and energy applications. ? 2025 Elsevier Inc. All rights reserved.